The Dynamics of Tourism in Sambangan Village, Buleleng, Bali - Sanjaya, Rindo Bagus; Christian Lilik Henri Setiawan Nivak (KRITIS, 2024)
ABSTRACT The successful development of tourism in a region is closely tied to tourism awareness and effective destination management. Sambangan Village in Bali is an up-and-coming tourist destination known for its nature-based attractions. The local community firmly believes that the village's success is contingent upon their awareness and active participation. This study delves into the tourism dynamics of Sambangan Village by examining insights from tourism managers associated with the local community's Tunjung Mekar Tourism Awareness Group (POKDARWIS Tunjung Mekar). The study utilized qualitative methods, including in-depth interviews with the chairman of POKDARWIS Tunjung Mekar, local community members from Sambangan Village, and travel agents from Lovina and Kuta Beach. The findings revealed that Sambangan Village has implemented development strategies that impact its tourism dynamics, including strengthening tourism products and institutional capacity, enhancing tourist safety and comfort, as well as promotional and marketing efforts. The study aims to provide valuable recommendations for the development of similar tourism destinations across Indonesia. Keywords: tourism awareness, dynamics of tourism, community-based tourism, Sambangan Village, Sambangan Secret Garden